2013
DOI: 10.2217/fca.13.34
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Vascular Complications in Peripheral Extracorporeal Membrane Oxygenation Support: A Review of Techniques and Outcomes

Abstract: Peripheral venoarterial extracorporeal membrane oxygenation support provides prolonged support in the event of acute or acute-on-chronic cardiac and/or respiratory failure. This support serves as a bridge to recovery, decision-making, heart transplantation or ventricular-assist device implantation. It can be implanted either through a percutaneous approach using Seldinger's technique or via an open approach via the common femoral artery or the axillary artery. Early and late arterial vascular complications rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 26 publications
1
32
2
Order By: Relevance
“…In comparison, axillary artery cannulation results in antegrade aortic flow and is preferred for patients with preserved left-ventricular function. 15 Compared with femoral percutaneous cannulation, the axillary approach usually requires surgical dissection and is more time-consuming. In our patient, femoral artery access was chosen due to severe hemodynamic instability and need for rapid deployment of ECMO.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, axillary artery cannulation results in antegrade aortic flow and is preferred for patients with preserved left-ventricular function. 15 Compared with femoral percutaneous cannulation, the axillary approach usually requires surgical dissection and is more time-consuming. In our patient, femoral artery access was chosen due to severe hemodynamic instability and need for rapid deployment of ECMO.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, a recent metanalysis reviewing 20 studies comprising 1886 patients revealed a pooled estimate of rate of limb ischemia as high as 16.9% (12.5-22.6%); compartment syndrome at 10.3% (7.3-14.5%) and amputation at 4.7% (2.3-9.3%) [13]. Other contemporary, smaller reviews report limb ischemia in range of 4.4-19% and 11-52% [14,15]. The variation among published literature in incidence of limb ischemia and related complications may be due to difference in inclusion criteria of patients, difference in definition of limb ischemia and publication bias.…”
Section: Incidence Of Limb Ischemiamentioning
confidence: 99%
“…52 Because ECMO for PH traditionally requires a venoarterial configuration to bypass the pulmonary vascular bed, such support may be associated with the complications of femoral arterial cannulation. 53,54 The development of several novel upper-body configuration strategies minimizes these risks and facilitates mobilization. Internal jugular venous drainage may be combined with subclavian arterial reinfusion via an end-to-side graft.…”
Section: Pulmonary Hypertensionmentioning
confidence: 99%